GREENHOUSE GAS EMISSION CONTROL IN NATIONAL DEVELOPMENT - Naseha Elkarima; Muammar Khaddafi; Sri Yanti; Nolla Puspita Dewi; Rico Nur Ilham (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Environmental issues such as global warming, the greenhouse effect, and drastic climate change, as well as social issues such as meeting the needs of both workers and interested parties continue to increase, and urge the development of innovative financial products. Manufacturing companies are currently in the spotlight of various interested parties, there are 8 industrial sectors that contribute large amounts of carbon emissions, namely: cement industry, steel industry, pen and paper industry, textile industry, ceramic industry, fertilizer industry, petrochemical industry, and food and beverage industry. This concern for the environment must continue to be improved seeing that the impact of company operations is very significant starting from the greenhouse gas effect which continues to increase every day. As a country committed to the climate change control agenda, Indonesia has developed regulations, action programs and systems and mechanisms to reduce GHG emissions to meet the Nationally Determined Contribution (NDC) target and control GHG emissions in national development. One of the supporting mechanisms developed is the Value of Carbon Economy.